Christian ethics the end of the law - Cunningham, David S. 1961- (London New York Routledge, 2008)
"Christian Ethics" provides a biblical, historical, philosophical and theological guide to the field of Christian ethics. Prominent theologian David S. Cunningham explores the tradition of 'virtue ethics' in this creative and lively text, which includes literary and musical references as well as key contemporary theological texts and figures. Three parts examine: the nature of human action and the people of God as the 'interpretative community' within which ethical discourse arises the development of a 'virtue ethics' approach, and places this in its Christian context significant issues in contemporary Christian ethics, including the ethics of business and economics, politics, the environment, medicine and sex. This is the essential text for students of all ethics courses in theology, religious studies and philosophy.
Narrating the Christian lifePracticing the Christian life -- Living the Christian life.
Includes bibliographical references (p. [375]-385) and index
Formerly CIP
Narrating the Christian life -- Practicing the Christian life -- Living the Christian life
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Christian Ethics